(untitled) (Journal of Informatics Education and Research, 2024)
This study investigates academic stress among senior secondary school students, focusing on gender differences and the types of schools attended. The problem was framed as: "A Study of Academic Stress in Relation to Gender and Types of Schools." The objectives were to examine the levels of academic stress among male and female students and to analyze stress levels between students in government and private schools. The hypotheses stated that there is no significant difference in academic stress between male and female students and no significant difference between students in government and private schools. A descriptive survey method was employed to collect data from 600 students across three districts in Haryana—Bhiwani, Charkhi Dadri, and Rohtak. The tool used was the "Scale for Assessing Academic Stress" by Udai Kumar Sinha, and statistical techniques such as mean, standard deviation, and the ’t’ test were applied. Findings revealed that male students experience higher levels of academic stress than female students. Government school students also reported significantly greater academic stress compared to private school students. These results suggest the need for gender-sensitive interventions and enhanced resources in government schools to reduce academic stress and promote a supportive learning environment.